Penerapan Model Kebijakan Kepemilikan Kendaraan sebagai Upaya Mengurangi Kadar Emisi Karbon Dioksida di Indonesia dan Singapura - Miftah Anandini; Dian Azmi Khadijah; Febri Dwi Saputri; Shofiyah Aulia; Mawar Mawar (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The issue of carbon emissions in the transportation sector is a major challenge for developing countries like Indonesia, which experiences a sharp increase in vehicle ownership each year. This study aims to compare vehicle ownership policies between Indonesia and Singapore as strategies for reducing carbon dioxide (CO₂) emissions. Using a qualitative method with a comparative study approach, data were obtained through literature analysis on regulations, policies, and secondary emission data. The results indicate that Indonesia focuses more on incentives and emission standards tightening, while Singapore enforces strict vehicle ownership restrictions through the Certificate of Entitlement (COE) system, additional taxes, and vehicle age limitations. The novelty of this study lies in its comparative focus on vehicle ownership regulations as policy instruments for emission control—an aspect rarely examined in the Southeast Asian administrative context. The study concludes that strict and structured regulations, supported by efficient public transport systems, are key to reducing transportation-related carbon emissions.